Pengaruh Pembelajaran Berbasis Masalah Sistem Daring Berbantuan Google Classroom Kombinasi Zoom Terhadap Hasil Belajar Ekonomi Mikro dan Tanggung Jawab Pada Mahasiswa Program Studi Pendidikan Ekonomi Dimasa New Normal - Rindrayani, Sulastri Rini (Efektor, 2021)
Online learning in all education levels, from elementary school up to university levels is one effect of the outbreak of Covid-19 pandemic. This research was aimed at analyzing the effectiveness of problem based online learning using the combination of google classroom and zoom on students' microeconomics learning outcome and responsibility.The data were collected by using subjective test on students’ learning outcome and questionnaire on students’ responsibility. Further, the data were analyzed by using One Way Manova, which simultaneously showed that there is a significant difference on Microeconomics 1 learning outcome and responsibility of students who experienced problem based on the online learning using combination of Google Classroom and Zoom, proven by F count of Pillai’s Trace 0f 66.789 at sig. 0.00 < 0.05. In univariate, there is a significant difference on Microeconomics 1 learning outcome of students who experienced problem based online learning using combination of Google Classroom and Zoom, proven by F count of 135.215 at sig. 0.00 < 0.05. However, there is no significant difference on responsibility of students who experienced problem based online learning using combination of Google Classroom and Zoom, proven by F count of 0.119 at sig. 0.731 > 0.05.